Polska – Kazachstan: perspektywy współpracy i polskie interesy w Azji Centralnej - Waśkiel, Tomasz (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2016)
In August 2016 Poland was visited by Nursultan Nazarbaev, the president of Kazakhstan. During the visit various agreements were signed whose aim is to strengthen cooperation between the two countries. Considering Polish interests, energy cooperation and Polish diaspora in Kazakhstan are two of the most weighty issues. Apart from analysing the current state of Polish-Kazakh relations the article attempts to describe the perspectives of their development. As the region of Central Asia is often treated as a whole, the relations with Kazakhstan have been presented in the context of relations with other countries of the area.
Keywords: Kazakhstan; Poland; economic cooperation; energy cooperation; Polish diaspora